Septic sacroiliitis in the late postpartum due to Escherichia coli (2016)
Septic sacroiliitis is an unusual condition, and due to its non-specific symptoms, the diagnosis is often delayed. It should be suspected in cases in which inflammatory back pain and systemic inflammatory signs co-exist, especially in people with risk factors, such as postpartum. The case is presented of a woman, who in the late postpartum, presented with sacroiliitis and severe sepsis due to Escherichia coli. This is the second report of a case of septic sacroiliitis due to Escherichia coli associated with pregnancy. © 2016 Asociación Colombiana de Reumatología. Published by Elsevier España, S.L.U. All rights reserved.